ANALISIS HASIL BELAJAR SISWA SESUDAH GURU MEMAKAI PBL DALAM PENGEMBANGAN LKPD MATEMATIKA DI SD: STUDI LITERATUR - Silalahi, Jernita Damayanti; Tumanggor, Frans Lolo Osvaldo; Syahrial, S (Universitas Negeri Medan, 2024)
Three main focuses are discussed in this research: the effect of problem-based E-LKPD learning on improving students' mathematical problem-solving capabilities; the applicability of problem-based Mathematics E- LKPD developed based on PBL in both high and low grades; and the direction of problem-based E-LKPD development. The purpose of this research is to prove whether PBL is effective in fostering students' mathematics learning outcomes in elementary school by using E-LKPDs. This research uses a literature study. The focus of the research is on activities related to library data collection, reading as well as recording, and managing research data factually, regularly, examining, and critically related to the PBL model to improve student learning outcomes in elementary school mathematics. The results of the study can conclude that PBL- based LKPD can improve student learning outcomes. Keywords: LKPD, Mathematics, Problem-Based Learning, Learning Outcomes.